2019
DOI: 10.1111/wrr.12709
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported scar quality of adults after burn injuries: A five‐year multicenter follow‐up study

Abstract: Scar formation is an important adverse consequence of burns. How patients appraise their scar quality is often studied shortly after sustaining the injury, but information in the long‐term is scarce. Our aim was, therefore, to evaluate long‐term patient‐reported quality of burn scars. Adults with a burn center admission of ≥1 day between August 2011 and September 2012 were invited to complete a questionnaire on long‐term consequences of burns. We enriched this sample with patients with severe burns (>20% total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 39 publications
4
53
2
Order By: Relevance
“…Studies that investigated patient-and observer-reported scar quality of burn wounds also found that items on color were rated worse than other items. 7,21 The severe scores and reduction over time that we found for patientreported itching are also in accordance with previous studies regarding burn and linear scars. 7,12,13 The items pliability, thickness, and relief seem of less importance in our study population than to populations with burn scars or linear scars.…”
Section: Discussionsupporting
confidence: 92%
“…Studies that investigated patient-and observer-reported scar quality of burn wounds also found that items on color were rated worse than other items. 7,21 The severe scores and reduction over time that we found for patientreported itching are also in accordance with previous studies regarding burn and linear scars. 7,12,13 The items pliability, thickness, and relief seem of less importance in our study population than to populations with burn scars or linear scars.…”
Section: Discussionsupporting
confidence: 92%
“…And a changed appearance might have a greater impact on a females life [46]. Studies focusing on other outcomes in burns found that female burn patients had higher levels of fatigue, a worse opinion about their scars, more difficulties with social participation, and mortality rates are higher than in male patients [46][47][48][49]. With respect to longer LOS, many studies have shown that patients with a prolonged hospital stay have a diminished HRQL, both shortly and longer after burns [10,41].…”
Section: Measurement Point No Of Studies Contributing No Of Patients mentioning
confidence: 99%
“…As reported in the result section, we found that female sex was the only factor that seemed to negatively influence the self-reported total POSAS scar scores. Two recent studies, from 2018 and 2019 [120,126], supported this finding, showing that women rated their overall scar score significantly higher than men. Another study from 2014, showed that women least preferred donor sites on the thigh, compared with all other locations [127].…”
Section: Factors Predicting the Development Of Scarring At Donor Sitesmentioning
confidence: 76%